(untitled) (Research, Society and Development, 2021)
This article carries out an analysis of the implementation of the models Information Technology and Communication (ICT) Governance in the scope of the Brazilian Judiciary in the light of Institutional Theory and good practices internationally recognized such as the COBIT framework and regulations published by the Federal Court of Auditors (FCA) and the National Council of Justice (NCJ). For this, it was performed a comparative analysis of the results of the questionnaire iGovTIC-JUD, published by CNJ in 2016 and 2017. It was sought to identify whether the Courts, specifically those of the State Justice, had their models of ICT Governance implemented and/or were improved in this period. It was observed that the implementation of ICT Governance models figures a recent thematic in these institutions and, although mechanisms of coercive isomorphism have been employed, its effective institutionalization within these Courts is still slow and emblematic, with markedly weakened advances regarding the effectiveness of its controls.